The Benefaction of EFL Teacher Communication Skills on Students’ Oral Communication Performance in Online Class - Nur Aeni; Muthmainnah Muthmainnah; Selvi Panggua (Celebes Journal of Language Studies, 2021)
Nowadays, 4.0 Education 4.0 is a new paradigm in educational context in which it focuses on the innovation and maximizes the use of information, internet, and technology. Teacher has some essential roles in the classroom. One of those roles is teacher as a facilitator and communicator. Teachers facilitate the students in the classroom. They help them in conducting the teaching and learning process. Teachers talk to the students during the activities in the classroom. It is important to know whether the teacher applies the communication skills properly in the classroom or not; and the students’ perception about the teachers’ communication skills contribution on their speaking performance. This study applied qualitative method. The data were collected by observation, questionnaire, and interview. The researcher collected, analyzed and interpreted a variety of data to reveal the kinds of communication skills that were used by the lecturer in the class, and then found the students’ perception about the lecturer communication skills toward their oral communication performance. The data resources were the lecturers’ verbal and non-verbal communication applied in the classroom. The sources of the data based on the observation taken from one English lecturer in public university and one of English lecturer in private university. In addition, the interview taken from students of those lecturers. The non-verbal communication skills that were applied by the teachers. Each communication skill applied by the teacher had effect on students’ oral communication performance, whether it was directly or indirectly effective on students’ oral communication performance. Not all verbal communication could be effective directly on the students’ oral communication performance or not all non-verbal communication skills could be effective on the students’ oral communication performance.